The role of KIR genes and ligands in leukemia surveillance - Babor, Florian; Fischer, Johannes C.; Uhrberg, Markus (Frontiers in Immunology, 2013)
The anti-leukemic potential of natural killer (NK) cells has been of rising interest in recent years. Interactions between inhibitory killer immunoglobulin-like receptors (KIR) and HLA class I ligands seem to be critically involved in the immunosurveillance process. It is also well established that mismatching of HLA class I-encoded KIR ligands in the setting of hematopoietic stem cell transplantation leads to allorecognition of leukemic cells by NK cells, which is in line with the concept of missing-self recognition. Recent data now suggest that KIR gene polymorphism constitutes another important parameter that needs to be taken into account for selection of suitable stem cell donors. Moreover, the role of KIR gene polymorphism for predisposition to leukemia is a current matter of debate. Here, we would like to review the role of KIR function and genetic polymorphism for recognition of leukemia and discuss the impact of these findings for developing novel concepts for NK cell-based immunotherapy strategies.